Photonic Generation of Frequency and Bandwidth Multiplying Dual-Chirp Microwave Waveform - Xuan Li; Shanghong Zhao; Zihang Zhu; Kun Qu; Tao Lin; Dapeng Hu (IEEE Photonics Journal, 2017)
A photonic approach to generate a frequency and bandwidth multiplying dual-chirp microwave waveform using a single dual-polarization quadrature phase shift keying (DP-QPSK) modulator is proposed and demonstrated. In the proposed scheme, an RF carrier is applied to one QPSK modulator and a baseband single-chirp waveform is applied to another. By setting the driving signals applied to the modulator and adjusting the dc bias phases in the modulator, high-order optical sidebands can be obtained with the optical carrier suppressed. After optical to electrical conversion, a frequency-doubling and bandwidth-quadrupling, or frequency-quadrupling and bandwidth-octupling dual-chirp microwave can be generated. The approach is verified by simulation. Dual-chirp microwave waveforms with 16-GHz central frequency, 2048-MHz bandwidth and 32-GHz central frequency, 4096-MHz bandwidth are generated through an 8-GHz RF carrier and 512-MHz bandwidth baseband signal. The generated dual-chirp microwave waveform can be used in a radar system to improve its range-Doppler resolution.